Accounting ethics: The invisible fortress in the face of corporate fraud. A systematic review - Damian-Sandoval, Luz Maria; Pisfil-Benites, Nilthon; Collazos-Alarcón, Mercedes Alejandrina; Vidal-Taboada, Silvia Lourdes (LACCEI, 2024)
Corporate fraud has been a growing concern in the business world in recent years, due to the numerous cases of accounting fraud that have occurred in various countries, a situation that has called into question the ethics of CPAs, therefore, the present systematic review aims to explore in depth the scientific approach related to corporate fraud and the professional ethics of the CPA. The development of this study included an exhaustive search and evaluation of scientific articles published in specialized journals in order to obtain accurate information. For this purpose, two digital databases were consulted: Scopus and Ebsco. Within these, 55 articles were found, of which 25 were considered, based on inclusion and exclusion criteria. Finally, it is concluded that corporate fraud is related to professional ethics in students of Public Accounting, because the accountant with comprehensive training has the skills to implement internal control systems to mitigate business problems, contributing to the prevention of irregular practices and behaviors. Recommendations are also proposed to extend research in this area of investigation.